Вышгородская икона святых князей Бориса и Глеба: истоки образа и эволюция иконографии - Мусин, А.Е. (Археологія і давня історія України, 2017)
В статье реконструируется древнейшее иконное изображение свв. князей Бориса и Глеба XI в. из
церкви в Вышгороде, отмечается роль латинской
традиции в сложении его иконографии и влияние
искусства крестоносцев на появление новых икон святых князей в конце XII—XIII в. У статті подано широкий аналіз еволюції іконографії свв. князів Бориса і Гліба в Східній Європі в
XI—XIII ст. Автор демонструє візантійські і європейські елементи в їхній репрезентації. The article presents a comprehensive analysis of the
development of the iconography of Saint Princes Boris
and Gleb in the Eastern Europe, 11th—13th century.
The author shows byzantine and western European
elements in the representations. The enigmatic composition
on the reliquary-cross and pendant icons where
saint brothers are depicted as donators must be interpreted
as a scene of aurum coronarium. Such iconography
of holy martyrs offering their crowns to Mather
of God was broadly presented in the Christian art of
Rom during the Late Antiquity and had its revival in
the mid — 11th century. Most probably it decorated the
frescos in the apse of the church in Vyshgorod build in 1072 by the Prince Izyaslav Yaroslavich who had intensive
contacts to the Latin Europe. Additionally, the Princes had been initially buried in medio ecclesiae according
Western and not Byzantine tradition. The new iconography where the saints are presented with their
swords should be regarded as crusader interpretation of the byzantine image and has nothing to the idea of
the originality of the Russian medieval art and special change in the Russian religious mind.